Aging Populations and Public Pension Schemes - Chand, Sheetal (Occasional Papers; Occasional Paper, 1996)
This paper discusses a study analyzing aging populations and public pension schemes. An aging society is characterized by a growing proportion of the retired to the active working population. The study examines the pension-related aging problem primarily from a fiscal perspective. It analyzes how prospective demographic developments that affect the proportion of the pensionable elderly affect pension outlays. It confirms that very serious fiscal stresses are in prospect for most industrial economies. Addressing such problems satisfactorily will require major actions early, given the long lead times involved in reforming a pension fund's financial position.